Physical mechanisms underpinning conductometric gas sensing properties of metal oxide nanostructures. Issue 1 (31st December 2022) - Leturcq, Renaud; Bhusari, Rutuja; Barborini, Emanuele
ABSTRACT: In the domain of gas sensing, metal oxide nanostructures have been demonstrated to have very attractive properties due to their large surface-over-volume ratio, combined with the possibility to use multiple materials and multi-functional properties. Here, we review the basic physical principles underlying the transducer function of metal oxide nanostructures, from single nanostructures to nanostructure networks. These principles have been adapted to describe the response of more complex nanostructures, such as heterostructures, combining two different metal oxide materials, or a metal with a metal oxide, in order to further enhance the sensitivity and selectivity of such devices. We finally present the activation of nanostructures by light exposure as a promising alternative to the standard method based on high temperature activation, which is earning increasing consensus in the perspective of low-power Internet of Things applications. Graphical abstract: uf0001